Analisis Kinerja Keuangan pada PT Kimia Farma Tbk (Periode 2019-2021) - Gani, Herlina; Tampubolon, Frances Roi Seston (LANCAH: Jurnal Inovasi dan Tren, 2024)
This study aims to analyze the financial performance of PT Kimia Farma Tbk during the period of 2019-2021 with a focus on profitability and liquidity ratios. The profitability ratios used in this analysis include Return on Assets (ROA), Return on Equity (ROE), and Gross Profit Margin (GPM). Meanwhile, the liquidity ratios analyzed are the Current Ratio and Quick Ratio. The data used in this research were taken from the annual financial reports of PT Kimia Farma Tbk published during that period. The results of the analysis indicate that PT Kimia Farma Tbk experienced fluctuations in profitability and liquidity performance over the past three years. ROA and ROE showed a significant decrease in 2020 due to the impact of the COVID-19 pandemic, but began to show signs of recovery in 2021. Gross Profit Margin also experienced a decrease in 2020, but there was a slight increase in 2021. On the liquidity side, the Current Ratio and Quick Ratio indicate that the company has adequate ability to meet its short-term obligations, although there was a decrease in 2020 due to a decline in revenue and an increase in operating costs during the pandemic. Overall, this research provides insights into how PT Kimia Farma Tbk managed their financial performance during a challenging period and demonstrates the company's efforts in post-pandemic recovery. This study is expected to serve as a reference for the company's management and other stakeholders in making strategic decisions to improve financial performance in the future.